Pengembangan Model Edupreneurship sebagai Upaya Peningkatan Daya Tarik Wisata Pantai Pudak, Kabupaten Blitar - Yuhanin Zamrodah; Luhur Aditya Prayudhi; Endah Siswati; Wahyu Dwi Lestari; Zainal Abidin Achmad; Diana Aqidatun Nisa (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2025)
The development of Pudak Beach, located in Ngadipuro Village, Wonotirto District, Blitar Regency, as a tourist destination is not simply about creating a tourist attraction, but rather a comprehensive strategy aimed at improving the welfare of the local community while preserving the environment. By optimizing the surrounding natural and cultural potential, investment in tourism can generate new employment opportunities, strengthen the creative economy sector, and increase local income—particularly through community-based tourism products and services. This community service program aims to develop an edupreneurship model that aligns with the social, economic, and cultural characteristics of the communities surrounding Pantai Pudak, Blitar Regency. The activities include needs assessment, entrepreneurship training (such as batik-making, visual branding, labeling and packaging), and digital marketing workshops. The program involved observation and interviews with Bumdes Estu Maju and Pokdarwis Dewatapuro, providing hands-on training while assessing participants’ enthusiasm and skill development throughout the process. The outcomes of the training and socialization activities successfully enhanced participants’ knowledge and understanding of hand-drawn batik techniques, visual branding, product labeling and packaging, as well as digital marketing. The significant improvement in skills and entrepreneurial capacity is expected to enable the community to manage local businesses more effectively, comprehend modern marketing concepts, and cultivate greater awareness of the importance of collaboration in sustaining and developing tourism potential. Furthermore, this program is expected to strengthen the community’s capacity as education- and economy-oriented tourism actors and provide recommendations for replicating the model in other coastal destinations. Abstrak Pengembangan Pantai Pudak yang terletak di Desa Ngadipuro, Kecamatan Wonotirto, Kabupaten Blitar ini sebagai destinasi wisata bukan sekadar menciptakan tempat wisata, melainkan strategi komprehensif yang bertujuan meningkatkan kesejahteraan masyarakat setempat sekaligus menjaga kelestarian lingkungan. Dengan mengoptimalkan potensi alam dan budaya di sekitarnya, investasi di bidang pariwisata dapat menciptakan lapangan kerja baru, memperkuat sektor ekonomi kreatif, dan meningkatkan pendapatan masyarakat, terutama melalui produk dan layanan pariwisata berbasis komunitas. Program pengabdian masyarakat ini bertujuan mengembangkan model edupreneurship yang selaras dengan karakteristik sosial, ekonomi, dan budaya masyarakat di sekitar Pantai Pudak, Kabupaten Blitar. Kegiatannya meliputi kajian kebutuhan, pelatihan kewirausahaan (pembuatan batik, visual branding, labelling, dan pengemasan produk), serta pelatihan pemasaran digital. Program ini melibatkan observasi dan wawancara dengan Bumdes Estu Maju dan Pokdarwis Dewatapuro, pemberian pelatihan praktis, sekaligus penilaian antusiasme dan pengembangan keterampilan peserta selama proses pelatihan. Kegiatan pelatihan dan sosialisasi ini berhasil meningkatkan pengetahuan dan pemahaman peserta tentang teknik batik tulis, visual branding, labelling dan pengemasan produk, serta pemasaran digital. Peningkatan keterampilan dan kapasitas kewirausahaan yang signifikan diharapkan dapat memampukan masyarakat mengelola usaha secara lebih efektif, memahami konsep pemasaran modern, dan menumbuhkan kesadaran yang lebih besar akan pentingnya kolaborasi dalam mempertahankan dan mengembangkan potensi wisata. Lebih lanjut, program ini diharapkan dapat memperkuat kapasitas masyarakat sebagai pelaku wisata yang berorientasi pada pendidikan dan ekonomi, serta memberikan rekomendasi untuk mereplikasi model ini pada destinasi pesisir lainnya. Kata Kunci: edupreneurship; wisata; pantai pudak